Prevalence of odontogenic cysts in oral and maxillofacial surgery department of hasan sadikin general hospital: 2 years retrospective study - Laksmitarani, Niken; Yusuf, Harmas Yazid; Adiantoro, Seto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Odontogenic cysts are cysts arising from the odontogenic epithelium. According to the World Health Organization in 2017, classification of odontogenic cysts are classified into cysts originating from inflammatory and developmental processes. Most cystic lesions of the oral and maxillofacial cavity are of odontogenic origin and have higher incidence than other body parts. This study to explain about prevalence of odontogenic cyst in RSUP Hasan Sadikin in 2019-2020 .Method: This study was a retrospective study that included 30 patients diagnosed with odontogenic cysts during 2019-2020. The data taken in each patient were age, gender, location of predilection, investigations, diagnosis, management, and recurrence of cases of odontogenic cysts.Result: A total of 15 patients had developmental odontogenic cysts and 15 had inflammatory odontogenic cysts. Most developmental cysts were 12 patients with dentigerous cysts, Odontogenci Keratocyst in 2 patients, and calcifying odontogenic cyst in 1 case. Inflammatory cysts were dominated by 15 patients with radicular cysts.Conclusion: Prevalence of odontogenic cyst was found more in female, with radicular cyst and location in the maxilla